Comparative efficacy of acupuncture and acupoint catgut embedding in diminished ovarian reserve: A prospective randomized controlled trial - Sanhong Liu; Cong Hou
Diminished ovarian reserve (DOR) is a significant health issue affecting women, leading to hormonal imbalances and infertility. Traditional Chinese Medicine (TCM) therapy plays a vital role in its treatment. This study aimed to compare the efficacy of traditional acupuncture and acupoint catgut embedding in improving ovarian function in women diagnosed with DOR. A single center randomized controlled trial was conducted with 61 participants aged 18-40 years diagnosed with DOR. Participants were randomly assigned to receive either acupuncture or acupoint catgut embedding. Primary outcomes included changes in follicle-stimulating hormone (FSH), estradiol (E2), anti-Müllerian hormone (AMH), antral follicle count (AFC), and menstrual cycle regularity. Quality of life was assessed using Kupperman scores and SF-36. Intra-group analyses showed significant improvements in FSH (p<0.001), E2 (p<0.001), AMH (p<0.001), and AFC (p<0.001) in both groups, with the acupoint catgut embedding group demonstrating superior improvements in FSH and luteinizing hormone (LH) levels (p=0.010 and p=0.022, respectively). Quality of life scores indicated better symptom control and general health in the catgut embedding group (p<0.001). Both acupuncture and acupoint catgut embedding were effective in enhancing ovarian function in women with DOR, with acupoint catgut embedding showing greater improvements in hormonal profiles and quality of life metrics. Further studies are warranted to confirm these findings and explore the underlying mechanisms.